Etnomatematika: Pengenalan Bangun Datar Melalui Konteks Museum Negeri Sumatera Selatan Balaputera Dewa - Lisnani Lisnani; Zulkardi Zulkardi; Ratu Ilma Indra Putri; Somakim Somakim (Institut Pendidikan Indonesia, 2020)
AbstrakEtnomatematika merupakan integrasi antara kebudayaan dan matematika sebagai salah satu usaha memperkenalkan budaya dan matematika secara bersamaan. Salah satu bentuk etnomatematika misalnya bangun bersejarah di kota Palembang yaitu Museum Negeri Sumatera Selatan Balaputera Dewa. Tujuan penelitian ini yaitu mengeksplorasi hubungan antara matematika dan budaya dalam seni arsitektur pada Museum Negeri Sumatera Selatan Balaputera Dewa dan mengenalkan konsep bangun datar melalui konteks Museum Negeri Sumatera Selatan Balaputera Dewa. Penelitian ini tergolong deskriptif kualitatif dengan studi pustaka. Subjek penelitian adalah salah seorang petugas Museum. Data dikumpulkan menggunakan prinsip etnografi melalui observasi, wawancara, dokumentasi, dan catatan lapangan. Teknik analisis data berupa hasil wawancara dan dokumentasi yang dikaitkan dengan kebudayaan dan matematika. Hasil penelitian ini yaitu eksplorasi hubungan antara matematika dan budaya, terutama dalam seni arsitektur pada Museum Negeri Sumatera Selatan Balaputera Dewa dan adanya konsep matematika yaitu bangun datar dari eksplorasi Museum Negeri Sumatera Selatan Balaputera Dewa. Ethnomathematics: Introduction of Plane Figure Through the Context of the South Sumatra State Museum Balaputera DewaAbstractEthnomathematics is an integration between culture and mathematics as an effort to introduce culture and mathematics simultaneously. One form of ethnomathematics, for example, is a historic building in the city of Palembang, namely the State Museum of South Sumatra Balaputera Dewa. The purpose of this research is to explore the relationship between mathematics and culture in architectural arts at the State Museum of South Sumatra Balaputera Dewa and introducing the concept of flat wakes through the context of the State Museum of South Sumatra Balaputera Dewa. This research is classified as descriptive qualitative with literature study. The research subject is one of the museum officers. Data collected using ethnographic principles through observation, interviews, documentation, and field notes. The data analysis technique was in the form of interviews and documentation related to culture and mathematics. The results of this study are the exploration of the relationship between mathematics and culture, especially in the art of architecture at the State Museum of South Sumatra Balaputera Dewa and the existence of a mathematical concept, namely the flat shape of the exploration of the Museum Negeri South Sumatra Balaputera Dewa.